Microbiologys Quality of Fish Sauce Tongkol (Euthynnus affinis) with Additions Pineapple Juice (Ananas comosus) - Irandha Citra Marasi Siahaan; Henny Adeleida Dien; Hens Onibala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Fish sauce is one of fish fishery product from fermentation process. In this study fish sauce madefrom Tongkol fish (Euthynnus affinis) that has high catching in North Sulawesi. This study aimed to makediversification product from Tongkol fish into fish sauce safe to eat. The research method applied wasexperimental laboratories. In this research was by additions (A) 0%, (B) 9%, (C) 12%, (D) 15% pineapplejuice and (G8) 8%, (G9) 9%, (G10) 10% salt and stored in an incubator at temperature 50ºC during 6,8, 10 days. Variable measured were Total Lactic Acid Bacteria, Total Plate Count, E.coli, Staphylococcussp, gram strain, pH, water consentration and organoleptic test. The result showed that sample D (D1G10)with additions pineapple juice 15% caused decrease total pathogen bacteria and caused increase lactic acidbacteria. Showed that Total Lactic Acid Bacteria, Total Plate Count, E.coli, Staphylococcus sp, gram strain,pH, water consentration, gram strain, organoleptic test with pineapple juice 15% was 1.0x102; 9.0x104; 5.46;69.14%; negative; 100 isolate positive shaped rod; the appearance 8; smell 8; taste 8. The result accordancewith Standard National Indonesia (SNI) and safe to eat.